Sorption isotherms of ingredients and diets for poultry (Research, Society and Development, 2020)
This study aimed to determine sorption isotherms of ingredient and poultry diet. The samples were encapsulated in capsules and dehydrated by oven-drying in a desiccator for more than 24 hours. The samples were transferred to desiccator containing water in the base and placed in the oven, with one sample of each material being removed at incremental intervals. The sample was weighed and for determination of water activity and for dry matter. The moisture and water activity data were evaluated by eight mathematical models. The GAB mathematical model fitted the experimental data to constitute the isotherm for each material. Type II sorption isotherms were found, except for BHT: demonstrated values that did not fit the isotherm determination. The hygroscopic behavior of the ingredients in ascending order were: L- threonine, limestone, BHT, DL- methionine, L-valine, L- tryptophan, phosphate, kaolin, vitamin supplement, salt, mycotoxin deactivator, pelleted rooster diet, mash rooster diet, mash layer diet, pelleted layer diet, corn, bacitracin zinc, vitamin mineral supplement, phytase, rice bran, wheat bran, mineral supplement, soybean meal, coccidiostat, L- Lysine HCl and choline chloride. Ingredients and diets have different hygroscopic behavior: can lead to deterioration and low accuracy in nutritional values of diet, since formulation is based on as-is fed basis.